2016
DOI: 10.3389/fimmu.2016.00423
|View full text |Cite
|
Sign up to set email alerts
|

Stat6-Dependent Inhibition of Mincle Expression in Mouse and Human Antigen-Presenting Cells by the Th2 Cytokine IL-4

Abstract: The C-type lectin receptors (CLRs) Mincle, Mcl, and Dectin-2 bind mycobacterial and fungal cell wall glycolipids and carbohydrates. Recently, we described that expression of these CLR is downregulated during differentiation of human monocytes to dendritic cells (DC) in the presence of GM-CSF and IL-4. Here, we demonstrate that the Th2 cytokine IL-4 specifically inhibits expression of Mincle, Mcl, and Dectin-2 in human antigen-presenting cells (APC). This inhibitory effect of IL-4 was observed across species, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 54 publications
7
21
0
Order By: Relevance
“…In contrast to GM-CSF and M-CSF BMMs, M-CSF/IL-4 BMMs did not produce inflammatory mediators in response to TDB despite showing the capacity to respond to LPS stimulation. Subsequent analysis of the cell surface expression levels of Mincle indicated that TDB induced rapid and significant increases in Mincle expression in GM-CSF BMMs but not for M-CSF/IL-4 BMMs, which is consistent with the earlier findings by Hupfer et al [44]. Moreover, while LPS priming increased Mincle expression and cytokine production by GM-CSF BMMs treated with TDB, LPS priming had no appreciable effect on Mincle expression or cytokine production by strongly M2-polarized macrophages treated with TDB.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast to GM-CSF and M-CSF BMMs, M-CSF/IL-4 BMMs did not produce inflammatory mediators in response to TDB despite showing the capacity to respond to LPS stimulation. Subsequent analysis of the cell surface expression levels of Mincle indicated that TDB induced rapid and significant increases in Mincle expression in GM-CSF BMMs but not for M-CSF/IL-4 BMMs, which is consistent with the earlier findings by Hupfer et al [44]. Moreover, while LPS priming increased Mincle expression and cytokine production by GM-CSF BMMs treated with TDB, LPS priming had no appreciable effect on Mincle expression or cytokine production by strongly M2-polarized macrophages treated with TDB.…”
Section: Discussionsupporting
confidence: 90%
“…4A). This observation is supported by earlier findings that show that IL-4 downregulates the expression of Mincle in human and mouse macrophages and DCs [44]. Priming of the macrophage populations with LPS enhanced TDB-induced increases in both Mincle expression ( Fig.…”
Section: Tdb Triggers Pro-inflammatory Activation Of Gm-csf Bmms Butsupporting
confidence: 88%
“…The inclusion of Mincle Ϫ/Ϫ BMM confirmed the specificity of staining with the 4A9 antibody in resting and stimulated BMM (see Fig. S3 in the supplemental material), consistent with previously reported results (41). Thus, TLR2 drives high-level Mincle expression in response to corynebacteria to optimize responsiveness to cell wall glycolipids of corynebacteria.…”
Section: Figsupporting
confidence: 90%
“…BMM were stimulated for 48 h in F-bottom 96-well cell culture plates. Receptor surface expression of Mincle was assessed by flow cytometry as described previously (41). Staining was performed by using anti-Mincle (clone 4A9; MBL) (24) as a primary antibody and anti-rat IgG1 conjugated to allophycocyanin (APC) as a secondary antibody (eBioscience, Frankfurt, Germany) at a final concentration of 1 g/ml for anti-Mincle and anti-rat IgG-APC.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with monocytes, the expression of the macrophage colony‐stimulating factor receptor (CSF1R, CD115) decreased and the expression of the mannose receptor (CD206) increased significantly for both Mo‐M and Mo‐DC 26,27 . Consistent with previous reports, these resting human cell populations showed low expression levels of Mincle 19,28,29 …”
Section: Resultssupporting
confidence: 87%